2010
DOI: 10.1007/s00056-010-1040-6
|View full text |Cite
|
Sign up to set email alerts
|

Halitosis, Oral Health and Quality of Life during Treatment with Invisalign® and the Effect of a Low-dose Chlorhexidine Solution

Abstract: This study provides evidence that Invisalign(®) treatment is characterized by only minimal impairment of overall oral health and the associated quality of life. Consequently, it appears unnecessary to recommend the general adjunctive use of a low-dose chlorhexidine mouthwash during treatment with Invisalign(®).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 32 publications
1
25
0
3
Order By: Relevance
“…The increased cooperation in terms of brushing we observed therefore generated an improvement in overall periodontal health. Excellent oral health in Invisalign® patients was also reported by Schaefer and Braumann [21], and they maintain that this was mainly due to improvement in the patient's awareness of oral hygiene, eliminating the need for regular oral hygiene instructions. This aspect can play a particularly important role in teenage patients, who are often difficult to motivate to practice sufficient oral hygiene at home.…”
Section: Diskussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The increased cooperation in terms of brushing we observed therefore generated an improvement in overall periodontal health. Excellent oral health in Invisalign® patients was also reported by Schaefer and Braumann [21], and they maintain that this was mainly due to improvement in the patient's awareness of oral hygiene, eliminating the need for regular oral hygiene instructions. This aspect can play a particularly important role in teenage patients, who are often difficult to motivate to practice sufficient oral hygiene at home.…”
Section: Diskussionmentioning
confidence: 88%
“…All the clinical measurements were taken by sitzende Apparaturen typischen Biofilms zu einem besseren Parodontalstatus als bei diesen führt. Invisalign®-Behandlungen scheinen im Hinblick auf die Weiterführung der häuslichen Mundhygiene in mehrerlei Hinsicht vorteilhaft zu sein [13], und verschiedene klinische Studien zu mit herausnehmbaren Alignern erbrachten keine Hinweise auf Gingivitis sowie bessere Gingival-und Plaqueindizes [14,15,21].…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Alternatively, Schaefer et al showed that removable orthodontic appliances, particularly invisible aligners, allow a more adequate oral hygiene 16 . About the correlation between halitosis and orthodontic aligners treatment it is shown that this kind of treatment did not lead to an increase of plaque and bacterial count, thus neither halitosis, nor oral dryness, nor high plaque or gingival index measurements were observed.…”
Section: Halitosis With Fixed Orthodontic Appliance Vs Removable Orthmentioning
confidence: 99%
“…The absence of ligatures should provide fewer retentive sites than other bracket ligation types 13 but, on the other hand, this theoretical advantage may be eliminated in reality because SLB consist in opening and closing mechanisms that may provide additional plaque retention sites 14,15 . Instead, with aligner devices, oral hygiene habits were very good 16 . The use of removable orthodontic appliances, particularly invisible aligners, allows adequate oral hygiene and can reduce the risk of dental and periodontal complications such as white spot lesions, caries and periodontitis 17 .…”
Section: Introductionmentioning
confidence: 99%